EXPERIMENTAL ANALYSIS OF VALUE OF ACCELERATION DUE TO GRAVITY USING PHYPHOX APPLICATIONS IN LEARNING PHYSICS IN SENIOR HIGH SCHOOL - Riztyana, Yunita
Experiments in physics have an important role, because the experiments illustrate various science process skills that are characteristic of learning physics in schools, especially at the high school level. However, experiments are often difficult to carry out for various reasons, one of which is the availability of experimental tools. Therefore an alternative solution is needed that can facilitate the implementation of physics experiments in high school. One of them is by using a smartphone by utilizing the Phyphox application. Phyphox utilizes various sensors contained in smartphones so that it can be used in various experiments including free fall motion experiments and mathematical pendulum, which can be applied in determining gravitational acceleration. However, the data generated through this application needs to be analyzed so that the level of accuracy can be seen. This final project research aims to compare the results of using the Phyphox application in free fall motion experiments and a mathematical pendulum to measure the acceleration of the earth's gravity in the physics learning process in high school. Based on the experiments that have been carried out, the value of gravitational acceleration obtained by using the Phyphox application in the free fall motion experiment is g = (9,7172 ± 0.02) m/s2 with R2 = 0.9999 while in the mathematical pendulum experiment g = 9,757 m/s2 where R2 = 0.994. The value of the Earth's gravitational acceleration from the two experiments is close to the previously calculated local gravitational acceleration value of 9,8 m/s2 with an error percentage of 0,5%. Based on these results, the Phyphox application can be used in physics experiments. In this final project, a free fall motion experiment and mathematical pendulum experiments module was also developed which refers to the basic competences of the grade X high school physics curriculum. The experimental module is adapted to the psycomotoric level of students and adapted to learning needs.